Public preference and participation in sustainable redevelopment of a closed landfill site in Ayer Hitam, Selangor, Malaysia - Nochian, Ashkan (2018)
Landfill is one of the most common methods of waste disposal besides incineration and recycling. However, issues arise with what to do at the end of their lifecycle. These issues are more pertinent with landfills that are located in or in close vicinity of urban areas where land is scarce, more valuable, and environmental hazards from landfills are taken seriously. Perhaps a solution to these closed landfills is to redevelop them into other successful sustainable uses. A sustainable redevelopment approach for landfill redevelopment (LR) reduces the risk of failure. One of the factors in sustainable development is public participation (PP) but to engage the public in the redevelopment effort is to consider public preferences towards the projects. Therefore, the goal of this study is to obtain and understand public preferences and affecting factors of different types of open spaces use for landfill redevelopment, public participation and affecting factors in landfill redevelopment, and the influence of the public preference on public participation for a sustainable a sustainable landfill redevelopment project. The study employed the explanatory sequential mixedmethods with closed-ended questionnaires distributed to 382 respondents to obtain public opinion regarding the Ayer Hitam Sanitary Landfill (AHSL) redevelopment. This survey was supported by interviews and field observations. A face-to-face interview was carried out with 13 AHSL site users and followed by field observations on major landfill issues and site users’ behavior. Results revealed that respondents preferred nature open space slightly higher than recreation and sport open spaces. In addition, perceived benefit and participant’s experiences were the most significant predictors for preference. The proposed model for public preference which includes the dependent and all independent and controlling variables was significant as a whole. Perceived benefit, concern, experience, age, and ethnic group all had significant relationships with preference. Regarding public participation (PP), the majority (75.7%) of the respondents agreed to participate in the LR project. Among factors affecting PP, preference, education and ethnic group were found to be significant. The model which consists of all independent and controlling variables with PP was found to be significant. Meanwhile preference, education and ethnic group had significant associations with PP. The primary implications of this study are that public preferences should be a core factor in the redevelopment plan because it increases public participation and therefore reduce the risk of project failure. The findings of this study may be useful for those dealing with landfills. The research findings, research framework, and methodology of the study can also be used for other studies related to landfill redevelopment as open spaces.